Pengaruh Green Perceived Value dan Green Perceived Risk terhadap Green Purchase Intention yang dimediasi Green Trust - Wicaksono, Riko Adi; Darpito, Surpiko Hapsoro (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The study aim to analzye the effect of Green perceived value and Green perceived risk on Green Purchase Intention mediated through Green trust. Green perceived value and green perceived risk are the independent variables considered. Green purchase intention is the dependent variable. Green Trust as a moderator. This research was a survey research with the data collection is a questionnaire. The population in this study are potential consumers of Le Minerale disposable gallons in Yogyakarta, The data used in this study is primary data obtained from the answers of 100 respondents with purposive sampling method. The data analysis method used is PLS (Partial Least Square) with the help of the SmartPLS version 3.2.9. The results showed that green perceived value has a positive and significant influence on green trust. Green perceived risk has a negative and significant impact on Green trust. Green trust has a positive and significant impact on Green purchase intention. Green perceived value influence Green purchase intention positive and significant. Green perceived risk has a negative and significant impact on Green purchase intention. Green trust mediates a positive and significant influence on Green perceived value and Green purchase intention. Green trust mediates a negative and significant influence on the relationship between Green perceived and Green purchase intention. Keywords:Green perceived value,Green perceived risk, Green trust, Green pruchase intention